Pembiayaan Defisit dengan Utang dan Ketahanan Fiskal di Indonesia - Suriadi, La Ode (Journal the Winners: Economics, Business, Management, and Information System Journal, 2013)
The focus of this study is to analyze the fiscal sustainability in Indonesia. To achieve these objectives, multiple regression model was constructed by the method of ordinary least squares (OLS). This model modified of the model of Buiter, Cudington, and Din. H.T. Data were collected from various sources such as the World Bank, Asian Development Bank, Bank of Indonesia, the Ministry of Finance of the Republic of Indonesia and the Indonesian Central Bureau of Statistics. The data are in the form of time series from 1980 - 2011. The results indicated that the budget deficit financing via debt (both foreign debt and domestic debt) still maintaining fiscal sustainability. This indication is seen from the change in value of the primary surplus that causes the debt ratio has decreased. Besides debt financing (both foreign debt and domestic debt) does not significantly causes the debt ratio increases.